Chemical kinetics of NO removal by pulsed corona discharges - Orlandini, Igor; Riedel, Uwe (Journal of physics. D, Applied physics, 2000)
Nitric oxides (NO and NO 2 ) and SO 2 emissions are a major environmental problem because of their negative influence on human health and vegetation. The federal regulations on limiting the pollution emitted by the engines of motor vehicles have triggered intense research on new techniques for the removal of these pollutants. New methods for exhaust gas cleaning are needed and among the several approaches to reduce the pollutant emissions, the non-thermal plasma technique shows promise (Luo J, Suib S L, Marques M, Hayashi Y and Matsumoto H 1998 J. Phys. Chem. A 102 7954). In this work, a volume-averaged model is presented that can describe the removal of NO x by the multi-pulse treatment of the exhaust gases at low temperatures and at atmospheric pressure in corona reactors. The model takes into account the production of active radicals after every discharge and the removal of NO by these radicals. Furthermore, the effect of ethene, one of the most important unburnt hydrocarbons in the exhaust gas, on the removal of NO is also investigated in this study. The effect of ethene has been investigated experimentally by several authors (Mizuno A, Chakrabati A and Okazaki K 1993 Non-Thermal Plasma Techniques for Pollution Control ed B M Penetrante and S E Schultheis (Berlin: Springer) p 165, Prather M J and Logan J A 1994 Proc. Combustion Institute 25 1513), but there are almost no studies which try to explain, in detail, the chemical processes in such a system. The detailed reaction mechanism used in this study consists of 443 elementary reactions and 50 chemical species. The results of our numerical simulations show good agreement with the experimental results published in the literature. Reaction flow analysis and sensitivity analysis are performed in order to identify the specific reaction paths and the rate-limiting reactions for typical operating conditions of pulsed corona reactors.